Strategi Growth-Oriented dalam Pengembangan Desa Wisata Aan di Kabupaten Klungkung Bali - Juliarta, Anak Agung Alit; Antara, Made; Surya, Ida Bagus Ketut (Jurnal Kajian Bali (Journal of Bali Studies); Vol 13 No 1 (2023): Volume 13 No 1 April 2023DO - 10.24843/JKB.2023.v13.i01.p10, 2023)
The study aims to formulate an effective development strategy for Aan Village by identifying strengths, weaknesses, opportunities, and threats. Aan tourism Village with a diversity of attractions should be well developed using an appropriate strategy. The study used a qualitative approach where the researcher became the research instrument. Data collection techniques used were observations, interviews, documentation, and triangulation techniques to check the credibility of the data. It was found that Aan Village has several potential tourist attractions such as landscapes, waterfall, river, culture, art, and history. The study found that growth-oriented strategies are suitable to be implemented in Aan tourism village which includes backward integration, forward integration, horizontal integration, market penetration, market development, and product development. Implementing those grand strategies will help Aan village meet the needs of the tourists  who, based on the recent trend, demand nature, eco, wellness, and adventure concepts.